2022
DOI: 10.1088/1742-6596/2388/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic features of diphenylaryethylenes and arylpolyenes having substituted groups in pairs

Abstract: The spectral and optical characteristics of 4,4′ substituted stilbene and diphenylpolyenes were determined depending on the nature of the substituents. It is established that as a result of the dipole-dipole interaction of Van der Waals forces and the entrainment of the electron energies of molecules in the studied compounds, a botochromic shift of the adsorption and luminescence spectra is carried out. It is determined that for 4,4′ substituted arylethylene molecules with protonadonnor substituted groups, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Analogous constancy of the electron spectra was previously observed in solutions of arylethylenes, aryl polyenes and food dyes. At the same time, the observed constancy of the electron spectra was attributed to the monomeric molecules of the studied compounds [17]. Based on these arguments, we concluded that at a concentration of 10 -5 ÷ 5 ×10 -5 mol, the "α"-carotenoid molecules will be in a monomeric state.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Analogous constancy of the electron spectra was previously observed in solutions of arylethylenes, aryl polyenes and food dyes. At the same time, the observed constancy of the electron spectra was attributed to the monomeric molecules of the studied compounds [17]. Based on these arguments, we concluded that at a concentration of 10 -5 ÷ 5 ×10 -5 mol, the "α"-carotenoid molecules will be in a monomeric state.…”
Section: Resultsmentioning
confidence: 62%
“…Carotenoids are natural pigments, they include more than a hundred natural compounds [1]. From the analysis of the literature data, it was determined that there is a relationship between the structures of caratinoids and the raman spectra of light.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [9,10] proposed a method for obtaining a mixture of carotenoids from dried plants by extraction using acetone or other ketone solvents. The authors [11,12] have developed a method in which dried plants are thermally treated for 1.9-07 hours, in which carotenoids undergo destruction, resulting in a poor-quality final product.…”
Section: Methodsmentioning
confidence: 99%
“…Spectroscopy makes it possible to obtain not only individual carotenoids, but also their derivatives. These studies make it possible to obtain pigments with the necessary chromaticity and specrally optical characteristics [14]. By the authors [15,16] a method for obtaining individual carotenoids has been developed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation